Desenvolvimento de uma sequência didática na Educação Infantil utilizando contos de fadas para exploração matemática - Moreno, Talita Lopes (Universidade Federal de São Carlos, 2024)
This work, conducted in the Graduate Program in Science and Mathematics Education, falls under Research Line I - Teaching and Learning in Science and Mathematics: Foundations, Processes, and Productions. The research addresses the theme of Mathematical Literacy in early childhood education and is based on questions regarding the integration of mathematical concepts into the daily lives of young children. The main objective is to analyze the impacts of implementing a didactic sequence involving a classic children's story on the process of Mathematical Literacy in early childhood education. This approach seeks to understand how the narrative of a story can be used as a pedagogical tool to facilitate the understanding and learning of mathematical concepts from early childhood. The methodology adopted is participant research, in which the researcher is actively involved in the implementation and data collection during the execution of the didactic sequence in a Kindergarten II class, composed of students aged between 5 and 6 years. Through this research, the aim is to highlight the relevance of Mathematical Literacy in conjunction with literacy in the mother tongue. The connection between classic children's literature and the acquisition of prerequisites for effective Mathematical Literacy is explored, with the intention of providing meaningful learning and promoting the cognitive development of children. The importance of establishing a relationship between the mother tongue and mathematics is emphasized, aiming to create a reflective and inclusive learning environment in which educators can foster the active participation of students in their own formation and social transformation. After the implementation and analysis of the Didactic Sequence, greater engagement and active participation of the children in activities involving mathematical knowledge were observed, contributing to the process of Mathematical Literacy. The structured activities made it possible to connect fairy tales, which are familiar stories in the children's universe, with mathematical themes, which were previously considered to be difficult.
Development of a didactic sequence in Early Childhood Education using fairy tales for mathematical exploration
Keywords: Cachinhos Dourados; Criança; Contação de história; Goldilocks; Child; Storytelling; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM